LABELLING DAN PACKAGING SEBAGAI USAHA PENINGKATAN NILAI JUAL TELOR ASIN DI DESA CIBODAS KECAMATAN TANARA KABUPATEN SERANG - Mada Badriyah, Ratu Dea; Anharudin; Miranty, Delsa (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
Most residents in Cibodas Village, one of the villages in Tanara District, Serang Regency, Banten Province, earn their living as farmers in rice fields and salted egg traders because some residents raise ducks. The Community Service Program, regarding making labels and packaging for salted eggs, is an effort to empower micro-producers to optimize the added value of their products. This activity aims to provide training and practice in label design so that participants gain knowledge about attractive designs and choosing suitable packaging materials. The participants' work reflects actual developments in visual and informative terms, contributing to improving brand image and potentially increasing sales. This program also encourages changes in business mentality and facilitates knowledge exchange within the community. In this activity, the method is carried out by identifying needs, planning, implementing, evaluating, and following up. The results of this program are increased knowledge and skills, changes in business approach, and improved brand image. This activity can also empower the local economy by developing micro-businesses and preserving traditional products.